A new product development learning model: antecedents and consequences of declarative and procedural knowledge. (1st January 2000) - Lynn, Gary S.; Akgun, Ali E.
Organisational learning is important, but we know surprisingly little about how to measure or manage it. This paper operationalises organisational learning in a new product development context and tests its effect on New Product Success (NPS) by studying 137 new product development projects. We found that two forms of organisational learning (Declarative and Procedural Knowledge) impact NPS. We also measured the antecedents of Declarative and Procedural Knowledge and explored their impact on Organisational Knowledge and New Product Success.